Meningkatkan Kemampuan Paedagogik Guru Melalui Pelatihan Pembuatan Soal Ujian Berbasis Pembelajaran Multiliterasi Terintegrasi Higher Order Thinking Skills di SD Negeri 2 Seulalah Langsa - Indah Fajarini; Coryna Oktaviani; Dini Fitria (Jurnal Ilmiah Wahana Pendidikan, 2022)
This service aims to provide training and guidance for teachers of SDN 2 Seulalah Langsa to make HOTS (Higher Order Thinking Skills) integrated multiliterate learning-based exam questions. This community service activity aims to (1) assist teachers in increasing understanding of evaluating learning outcomes, (2) increasing teachers' understanding of multiliteracy learning and HOTS questions, and (3) increasing teachers' pedagogical abilities in making HOTS integrated multiliterate learning-based exam questions, so that later HOTS questions are obtained in accordance with the standards of the 2013 Curriculum and Independent Learning. This community service activity was carried out in the form of short training for three face-to-face meetings by complying with health protocols and three online discussions. The activity was attended by elementary school teachers at SDN 2 Seulalah Langsa. The methods applied in the implementation of this activity are tutorial, discussion, simulation and demonstration methods. The result of this activity is an increase in the teacher's understanding of HOTS (Higher Order Thinking Skills) questions and the teacher's ability to make HOTS (Higher Order Thinking Skills) questions.